Printability and Properties of Conductive Inks on Primer-Coated Surfaces - Hector R. Mendez-Rossal; Gernot M. Wallner (International Journal of Polymer Science)
Conductive inks’ performance is affected by the printing conditions and the substrate’s properties. In this study, one graphite-, one polymer-, and two silver-based conductive inks were printed on four primer-coated metal substrates by screen printing. The compatibility and wettability between the inks and the primers were evaluated by infrared spectroscopy and surface energy measurements. The printed structures were characterized by laser confocal microscopy, peel-off tape testing, and four-point probe electrical resistivity testing. In general, silver inks exhibited the best performance in terms of printability and electrical conductivity. The graphite ink presented the worst printing, adhesion, and functional properties. The polymer-based ink revealed poor wettability but good adhesion and functionality. The surface roughness, energy, and polarity of the primer coating had no significant influence on the electrical conductivity of the printed inks.